Neutropenia induced by cytostatics in oncology - Yeris Leydis León Barrios; María Cristina Céspedes Quevedo; Ana Margarita Vinent Céspedes3 (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive and cross-sectional study of 330 patients with cancer, assisted in   "Conrado Benítez" Oncological Hospital in Santiago de Cuba, was carried out from June to December, 2014, to determine the presence of neutropenias induced by chemotherapy.  This disorder was present in 145 patients (44.0%). There was a prevalence of the 41-60 age group (51.0%), female sex (87.5%), breast cancer (64.8%), clinical stage II (50.3%), those affected patients with 2 neutropenia episodes (62.1%), as well as light (51.7%) and moderate grades (37.9%). One hundred eighteen patients responded to the treatment with ior® LeukoCIM (81.4%). There was no association between the different combinations of cytostatics, number of episodes and grades of that disease. The availability of the ior® LeukoCIM to treat this disorder will facilitate its prophylactic use and will improve these patients life quality.